Teacher Training To Increase Teacher’s Competency In Teaching Autism Child - Loi Sook Wei; Mohd Hanafi Mohd Yasin (Journal of ICSAR, 2017)
Autism teacher that is competence is able to educate autism child that are increasing throughout the year. The aim of this study is to identify the competency of special education teacher in teaching autistic child and curriculum in teacher training. This study used quantitative approaches and questionaire is built to collect the data. A total of 107 primary teachers in Jasin Melaka have been selected by purposive sampling for this survey. The study found that special education teachers are less competency in using evidence based teaching for autism. Data shows that most of the teachers have not received any training in how to teach autistic child during teaching training in university or teacher training center. This study is important to modify the current teacher training course related to autism to increase the quality of teachers.